Research on the Tensile Mechanical Properties of a Braided Corrugated Hose and Its Axial Stiffness Model - Dacheng Huang; Jianrun Zhang (Journal of Marine Science and Engineering, 2021)
Braided corrugated hoses are widely used in displacement compensation and vibration absorption environments due to their excellent flexibility and energy dissipation properties; however, the axial stiffness has rarely been discussed before as an important physical property of braided corrugated hoses. In this paper, the theoretical axial stiffness model for braided corrugated hoses is established based on the energy method and the theory of the curved beam. The influences of the braiding parameters of the metallic braided tube and the structural parameters of the bellows on the axial stiffness are also discussed. Through finite element tensile testing, the axial stiffness curves of the braided corrugated hose under different braiding angles and different wire diameters are obtained. The theoretical axial stiffness model is in good agreement with the simulation experiment, which reflects the nonlinear effects of the braiding angle and wire diameter on the braided corrugated hose. This paper provides an accurate method and basis for the design of braided corrugated hoses in the future.